Recovery of recombinant bromelain from Escherichia coli BL21-AI - Bala, Muntari; Salleh, Hamzah Mohd.; Amid, Azura; Mel, Maizirwan; Jami, Mohammed Saedi (Academic Journals, 2011)
In spite of the fact that commercial bromelain supplements are available in the market, to date, none of them are produced and formulated from recombinant forms. They are extracted and purified (often partially) from the stem and fruit of pineapple (Ananas comosus). This makes the production of bromelain very difficult, less reliable, often contaminated and expensive. In this study, a recombinant bromelain was expressed as soluble (active) and insoluble (inactive) enzyme in Escherichia coli BL21-A1. The enzyme fractions were purified using Ni-NTA His•Bind resin with the aid of an automated fast protein liquid chromatography (FPLC) system. Purification fold and percentage yield of the purified active bromelain were found to be 3.7 and 64%, respectively. SDS-PAGE results showed that the enzyme was purified to near homogeneity and the soluble form exhibited a single band with molecular weight of about 45 kDa.